Quantitative analysis of velopharyngeal movement using a stereoendoscope: accuracy and reliability of range images. (2nd January 2015) - Nakano, Asuka; Mishima, Katsuaki; Shiraishi, Ruriko; Ueyama, Yoshiya
Abstract: Objective : We developed a novel method of producing accurate range images of the velopharynx using a three-dimensional (3D) endoscope to obtain detailed measurements of velopharyngeal movements. The purpose of the present study was to determine the relationship between the distance from the endoscope to an object, elucidate the measurement accuracy along the temporal axes, and determine the degree of blurring when using a jig to fix the endoscope. Methods : An endoscopic measuring system was developed in which a pattern projection system was incorporated into a commercially available 3D endoscope. After correcting the distortion of the camera images, range images were produced using pattern projection to achieve stereo matching. Graph paper was used to measure the appropriate distance from the camera to an object, the mesial buccal cusp of the right maxillary first molar was measured to clarify the range image stability, and an electric actuator was used to evaluate the measurement accuracy along the temporal axes. Results : The measurement error was substantial when the distance from the camera to the subject was >6.5 cm. The standard error of the 3D coordinate value produced from 30 frames was within 0.1 mm (range, 0.01–0.08 mm). The measurement error of the temporal axes was 9.16% in the horizontal direction and 9.27% in the vertical direction. Conclusion : The optimal distance from the camera to an object is <6.5 cm. The present endoscopic measuring system can provide stable range images of the velopharynx when using an appropriate fixation method and enables quantitative analysis of velopharyngeal movements.